The Korean state and social policy : how South Korea lifted itself from poverty and dictatorship to affluence and democracy - Ringen, Stein (New York ; Oxford : Oxford University Press, 2011)
This book is about many things: development and modernization, dictatorship and democracy, state capacity and governance, social protection and welfare states, and Korean history. But finally it is about lifting social policy analysis out of the ghetto of self-sufficiency it is often confined to and into the center ground of hard political science.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Keywords: State, The; Democracy; Welfare state -- Korea (South); Korea (South) -- Social policy; Korea (South) -- Economic policy; Korea (South) -- Politics and government